Optimal Strategies for Indonesian Language Learning in Higher Education in The Globalization Era - Lina Marliana Dewi; Wahyudin Wahyudin; Fima Anggraeni; Mita Fauziah; Naiya Amalia (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to improve the quality of Indonesian language in learning at universities in the era of globalization. The good quality of the Indonesian language at this university can make it easier for students and lecturers to determine effective learning. This research is a type of qualitative research. With natural research subjects and objects, it is called naturalistic research, not manipulated or based on facts. This research used 55 respondents who were asked several questions about effective language learning strategies in the era of globalization. Serang Raya University is in first place for the most respondents. This research shows that learning methods such as questions and answers, presentations, discussions, and individual guidance are considered to be more helpful for students in understanding the material, thinking critically, and being able to develop students' communication skills. This research also shows that students are more enthusiastic and active in learning when lecturers use methods that involve interaction with students compared to using the lecture method. In the context of improving the quality of Indonesian language learning, collaborative efforts are needed between lecturers, students and universities to implement learning strategies and methods that are in line with the demands of globalization and are also the main focus in preparing students to face challenges in the era of globalization.